What drives the active involvement in business angel groups? The role of angels' decision-making style, investment-specific human capital and motivations - Bonnet, Christophe; Capizzi, Vincenzo; Cohen, Laurence; Petit, Aurelien; Wirtz, Peter (Journal of Corporate Finance, 2022)
This paper sheds light over the operations and internal structure of business angel groups (BAGs), a leading actor inside the informal venture capital industry, due to its capability to build cognitive resources and shared competencies that are eventually provided to funded ventures alongside equity capital. We develop a framework based on the role of business angels' decision-making style, human capital and motivation as major determinants of their active involvement in the many different activities performed by angel groups, either investment related activities or group management activities. Our empirical analysis relies on a novel survey-based dataset containing qualitative and quantitative information provided by the members of two large and rather homogeneous business angel groups located in France and in Italy. Results show that business angels with a control-oriented decision-making style tend to be more actively involved in key angel group activities. Human capital built through investment experience, retirement status, as well as initial motivation to join an angel group are also significant drivers of angel involvement in several key BAG activities.